2009
DOI: 10.1103/physrevlett.103.096401
|View full text |Cite
|
Sign up to set email alerts
|

Wave-Packet Dynamics in Chains with Delayed Electronic Nonlinear Response

Abstract: We study the dynamics of one electron wave packet in a chain with a non-adiabatic electronphonon interaction. The electron-phonon coupling is taken into account in the time-dependent Schrödinger equation by a delayed cubic nonlinearity. In the limit of an adiabatic coupling, the self-trapping phenomenon occurs when the nonlinearity parameter exceeds a critical value of the order of the band width. We show that a weaker nonlinearity is required to produce self-trapping in the regime of short delay times. Howeve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…These findings complement the recently published study of effects of the time-delayed nonlinear response on the transition to delocalization of wave packets [18]. Altogether, these results provide for an insight into the dynamics of localized patterns in slowly responding media.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These findings complement the recently published study of effects of the time-delayed nonlinear response on the transition to delocalization of wave packets [18]. Altogether, these results provide for an insight into the dynamics of localized patterns in slowly responding media.…”
Section: Discussionsupporting
confidence: 86%
“…In this regard, an essential issue is the dynamics of localized modes in media with the non-instantaneous nonlinear response. In particular, it was demonstrated that the relaxation of the nonlinearity has a strong influence on the wave-packet dynamics [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of electronic transport in low-dimensional nonlinear discrete lattices, one of the most known properties is the self-trapping (ST) phenomena. In general lines, ST occurs when the strength of the nonlinearity surpasses a threshold which is of the order the bandwidth for initially fully localized wavepackets [2][3][4][5][6]. In this case, the electron wavepacket remains trapped around the initial position with the probability of finding the electron at its initial position remaining finite in the long-time limit.…”
Section: Introductionmentioning
confidence: 96%
“…[5], and the influence of a temporal delay in the onsite nonlinearity on the self-trapping of discrete solitons was studied in Ref. [6].…”
Section: Introductionmentioning
confidence: 99%